Efek Fase Realimentasi Terhadap Perubahan Panjang Badan, Tinggi Pinggul Dan Tinggi Pundak Kambing Kacang Jantan Yang Digemukkan - Fransiskus P Bere Bria; Paulus Klau Tahuk; Gerson Frans Bira (LPPM Perjuangan University of Tasikmalaya, 2023)
This study aims to determine changes in the body length growth, hip height and shoulder height of male Kacang goats which are fattened during the realimentation phase. The cattle used were 15 male Kacang goats aged 12-14 months and weighing 10-14 kg. The fifteenth Kacang goats were grouped into three (3) treatments, each TO: Kacang goats without feed restrictions, T1: Kacang goats limited to 100% feed according to main life needs, T2: Kacang goats limited to 50% feed of basic life needs; each treatment contained 5 Kacang goats. This study used an experimental method according to a completely randomized design (CRD) procedure. The variables observed were body length, hip height and shoulder height. Research data were analyzed by ANOVA, followed by Duncan's test if the treatment has a significant effect. The results showed that body length, hip height and shoulder height of male Kacang goats fattened in the 3 groups of cattle were not significantly different (P>0.05). The body length of the TO, T1 and T2 treatments were 0.04 cm/day, 0.03 cm/day and 0.03 cm/day; the hip height of the TO, T1 and T2 treatments were 0.03 cm/day, 0.04 cm/day and 0.02 cm/day; and shoulder height in the TO, T1 and T2 treatments were 0.04 cm/day, 0.04 cm/day and 0.03. It can be concluded that young male Kacang goats that were fed 100% according to the main life needs (T1) and were limited to feeding 50% of the main life needs (T2) showed changes in body length, hip height and shoulder height which were not much different from the animals that received the normal feed (TO) in the realimentation phase. Feed restriction can spur the growth of Kacang goats in the realimentation phase because it increases feed consumption to catch up on growth.